Clinical and Immunological Spectrum of Systemic Lupus Erythematosus in Children - Kini, Sandesh; Y, Ramesh Bhat; Thunga, Chennakeshava; Shashidhara, Sowmya; Anand, Akshatha (Journal of Nepal Paediatric Society, 2020)
Introduction: Systemic Lupus Erythematosus (SLE) is an auto immune disorder affecting mainly adolescent females and young women of reproductive age. The disease is characterised by widespread inflammation of blood vessels and connective tissues due to the presence of anti-nuclear antibodies (ANA). There are limited number of studies from South India on paediatric lupus. Our objectives were to study the clinical and immunological features of childhood SLE along with treatment modalities and its outcome at the end of one year follow up. The correlation between various auto-antibodies and systemic involvement was also assessed.Methods: This was a retrospective observational study carried out in paediatric unit at a tertiary care centre in South India. Data was obtained through patient’s medical records. From April 2003 to April 2019, 32 children were diagnosed to have SLE as per the American college of Rheumatology 1997 criteria.Results: The study population included 32 children fulfilling the criteria. Female to male ratio was 4.3:1. The mean age at diagnosis was 11.52 years. The most common clinical manifestations were renal (87.5%) followed by haematological (81.3%), musculoskeletal (59.4%), mucocutaneous (53.1%) and nervous system (31.3%) involvement. All patients were positive for anti-nuclear antibodies. Anti-double stranded DNA (78.1%) was the most common auto-antibody profile followed by anti-ribosomal p protein (37.5%) and anti-nucleosome antibody (37.5%). During the follow up, 13 (40.6%) children attained complete remission, 10 (31.2%) went into partial remission and nine (28.1%) had persisting active disease. Conclusion: The clinical spectrum and outcome of paediatric SLE depends upon the age of presentation and number of organ systems involved at the time of diagnosis. Our study throws light on various aspects of SLE in children from developing countries like India.